Analyzing Process Types in Nigerian Newspapers Political Headlines Using Systemic Functional Linguistics (SFL) Transitivity Approach - Muhammad, Muhammad (International Journal of Linguistics, 2024)
Purpose: This study aims to examine the use of process types in Nigerian political headlines using the transitivity approach within the framework of Systemic Functional Linguistics (SFL). The purpose of the research is to understand how language is used to construct political narratives in Nigerian newspapers, focusing on the different process types—material, mental, relational, verbal, behavioral, and existential—that shape public perception of political events and actors. Methodology: The study adopts a qualitative method, analyzing 50 political headlines from five major Nigerian newspapers: Vanguard, Leadership News, Punch, Daily Trust, and The Guardian Nigeria. The headlines, selected from articles published between January 2024 and September 2024, are categorized and analyzed based on Halliday's transitivity framework. Findings: The findings reveal that material processes are the most frequently used, representing 48% of the headlines, followed by mental (32%), verbal (20%), and relational processes (10%). Existential and behavioral processes were minimally represented. These results suggest that political discourse in Nigeria is predominantly action- and belief-oriented, with a focus on tangible actions and the intentions of political figures. Unique Contribution to Theory, Practice and Policy: This study makes a unique contribution to theory by applying the SFL transitivity framework to Nigerian political headlines, expanding the understanding of how process types reflect political actions, intentions, and relationships. The findings have practical implications for media practitioners and politicians in crafting messages that effectively engage the public, emphasizing actions and beliefs to influence perception. From a policy perspective, the study suggests the need for greater media literacy to enable the public to critically assess political communication and its impact on public discourse.